The Composition of Major Minerals from the Buchim porphyry Copper Deposit, Republic of Macedonia (Geologica Macedonica, 2013)
Our current study of major ore and rock forming minerals enclosed the most important minerals within the Buchim ore deposit. Rock forming minerals were represented by plagioclase, K-feldspars, biotite and amphiboles. Beside their complex formulas those minerals have shown quite uniform compositions. Amphiboles were determined as hornblende, biotites were characterized by increased Fe and Ti and decreased Mg concentrations, plagioclases were determined as sanidine while K-feldspars were represented by albites and oligoclases. We have shown that the chalcopyrite composition is highly pure without any significant presence of Ni, Co, As and Sb (